Empowerment of Bamboo Rattan Weaving Craftsmen to Increase The Activities of Housewives in The Pasaman Regency - Nurhabibah, Nurhabibah; Syur'aini, Syur'aini (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
One Desa Tingkarang, Jorong VIII, Nagari Tarung-tarung Selatan, Kecamatan Rao, Kabupaten Pasaman, Provinsi Sumatera Barat, has abundant natural bamboo potential. Up to now, the utilization of bamboo has not been optimal in terms of both quantity and quality, even though bamboo can be used for various woven and non-woven crafts. Based on this, the village of Tingkarang, Jorong VIII, Nagari Tarung-tarung Selatan, Kecamatan Rao, Kabupaten Pasaman, Provinsi Sumatera Barat was chosen as the location to implement Community Empowerment (Pemberdayaan Kepada Masyarakat - PKM).The goal of the service is to produce bamboo woven crafts called "Tampah" with innovations in weaving techniques and colors. The partner group involved in the activity can apply bamboo craft weaving techniques for "Tampah" with various weaving styles and attractive colors. Through product innovation, the selling value of the products will increase, and there will be an improvement in the partners' ability to manage their business, including product innovation, marketing, and business bookkeeping.